2003
DOI: 10.1592/phco.23.4.526.32117
|View full text |Cite
|
Sign up to set email alerts
|

Use of Herbal Medicine by Elderly Hispanic and Non‐Hispanic White Patients

Abstract: As approximately half of the elderly patients stated that they used herbal medicines, health care providers should be knowledgeable about herbal remedies and provide reliable information to their patients about them in a nonjudgmental manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 8 publications
1
29
0
1
Order By: Relevance
“…[12][13][14][15][16][17][18][19] We carried out a multistage qualitative study using focus groups, in-depth interviews, and a video vignette to investigate processes of communication about TM/CAM. The 5 stages of the design were (1) focus groups composed of clinic staff and community key informants; (2) interviews of patients being seen in clinic; (3) interviews of clinicians in the same clinics; (4) an analytic focus group of clinicians from other clinics; and (5) refl ective interviews of community members and patients being seen in the clinics using a video vignette ( Figure 1 displays an overview of the study design).…”
Section: Designmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19] We carried out a multistage qualitative study using focus groups, in-depth interviews, and a video vignette to investigate processes of communication about TM/CAM. The 5 stages of the design were (1) focus groups composed of clinic staff and community key informants; (2) interviews of patients being seen in clinic; (3) interviews of clinicians in the same clinics; (4) an analytic focus group of clinicians from other clinics; and (5) refl ective interviews of community members and patients being seen in the clinics using a video vignette ( Figure 1 displays an overview of the study design).…”
Section: Designmentioning
confidence: 99%
“…15 Over one-half (52.0%) of the patients purchased their herbs in drugstores or groceries, where pharmacists would be available, but none of them received any herb information from the pharmacist. 17 Another study found that more practicing pharmacists, compared with pharmacy students, felt that pharmacists should not become practitioners of CAM (26.6% vs 0.0%). 18 This underscores the need for physicians to recognize an even greater responsibility to provide their patients with reliable information about herbs and to be particularly cognizant of the need to do so for their Hispanic population.…”
mentioning
confidence: 99%
“…Based on the initial literature search identifying the most commonly used herbal medicines as well as available data regarding commonly used herbals in patients with medical conditions frequently seen in hospice, 37 herbal medicines and supplements were included in the survey (Table 2). 16,[23][24][25][26][27][28][29][30][31] Participants were asked to rate their agreement on a scale of 1 to 5 (with a score of 1 equivalent to strongly disagree to 5 meaning strongly agree) for each medicine regarding four areas: high potential for use in hospice patients, high potential for serious adverse effects, high potential for serious drug interactions, and recommendation to include the medication on a list that hospice nurses ask about on every admission. In addition, participants were given the opportunity to list other herbals or supplements not included in the 37 medications that should be considered, as well as to state other general concerns regarding herbal use in hospice patients.…”
Section: Methodsmentioning
confidence: 99%